INFLUENCE OF GLUCOCORTICOSTEROIDS ON THE STATE OF THE VEGETATIVE NERVOUS SYSTEM DURING ACQUIRED MYOPIA IN SCHOOL AGE CHILDREN - Otabek A. Ikromov (Central Asian Journal of Medicine, 2025)
According to research data, the levels of hormones, particularly glucocorticoids and steroids, have a significant impact on the condition of connective tissue. Since the eye’s sclera consists of connective tissue, it undergoes changes when the levels of hormones, particularly cortisol, vary. Changes occur in the chemical composition and structural units of the sclera. This occurs due to changes in metabolic processes, in which cortisol is directly involved. It affects the processes of collagen anabolism and catabolism. Collagen is a connective tissue structure of the eye’s sclera, which participates in the development of myopia. Also, researchers argue that cortisol levels in children with myopia have a certain effect on the tone of the autonomic nervous system. However, data on this is insufficient. To resolve this issue, this research was conducted. It is necessary to determine the state of the sclera and autonomic nervous system in various levels of cortisol in acquired myopia in children and adolescents, which proceeds without complications.